(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3gPg CHhGH GdCSeGA , HGH aYd ,HaJM GdaGA (B: (3H(B: (3gh GdMH MGTjI LeY MHI QLY hjbGd QLd NH Ci bQHR s
(3GdfSNI JJab ai BNQgG eY BNQ fSNI edi edc (B- (3WgQGf (B345 (3HGNJdGa ai HYV GdCdaGX cJHJ HYV GdYfhGfGJ HGdMeQIs
(3hGdeNWhWI cGfJ ai SfI (B1030 (3g` ai MhRI GdMSjf Hf GdbGSe UGMH cJGH GdZGjIs
(3HBNQgG JbQjX ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs